Association between lactate/albumin ratio and all-cause mortality in critical patients with acute myocardial infarction - Wang, Danni; Luo, Chaodi; Li, Qian; Zheng, Tingting; Gao, Pengjie; Wang, Boxiang; Duan, Zhenzhen (Scientific reports, 2023)
It has been demonstrated that lactate/albumin (L/A) ratio is substantially relevant to the prognosis of sepsis, septic shock, and heart failure. However, there is still debate regarding the connection between the L/A ratio and severe acute myocardial infarction (AMI). The aim of this study is to determine the prognostic role of L/A ratio in patients with severe AMI. Our retrospective study extracted data from the Medical Information Mart for Intensive Care III (MIMIC-III) database, included 1,134 patients diagnosed with AMI. Based on the tertiles of L/A ratio, the patients were divided into three groups: Tertile1 (T1) group (L/A ratio<0.4063, n =379), Tertile2 (T2) group (0.4063≤L/A ratio≤0.6667, n =379), and Tertile3 (T3) group (L/A ratio>0.6667, n =376). Uni- and multivariate COX regression model were used to analyze the relationship between L/A ratio and 14-day, 28-day and 90-day all-cause mortality. Meanwhile, the restricted cubic spline (RCS) model was used to evaluate the effect of L/A ratio as a continuous variable. Higher mortality was observed in AMI patients with higher L/A ratio. Multivariate Cox proportional risk model validated the independent association of L/A ratio with 14-day all-cause mortality [hazard ratio (HR) 1.813, 95% confidence interval (CI) 1.041-3.156 (T3 vs T1 group)], 28-day all-cause mortality [HR 1.725, 95% CI 1.035-2.874 (T2 vs T1 group), HR 1.991, 95% CI 1.214-3.266 (T3 vs T1 group)], as well as 90-day all-cause mortality [HR 1.934, 95% CI 1.176-3.183 (T2 vs T1 group), HR 2.307, 95% CI 1.426-3.733 (T3 vs T1 group)]. There was a consistent trend in subgroup analysis. The Kaplan-Meier (K-M) survival curves indicated that patients with L/A ratio>0.6667 had the highest mortality. Even after adjusting the confounding factors, RCS curves revealed a nearly linearity between L/A ratio and 14-day, 28-day and 90-day all-cause mortality. Meanwhile, the areas under the receiver operating characteristic (ROC) curve (AUC) of 14-day, 28-day and 90-day all-cause mortality were 0.730, 0.725 and 0.730, respectively. L/A ratio was significantly associated with 14-day, 28-day and 90-day all-cause mortality in critical patients with AMI. Higher L/A ratio will be considered an independent risk factor for higher mortality in AMI patients.